Performance simulation and thermodynamics analysis of hydrogen production based on supercritical water gasification of coal. (13th August 2021) - Chen, Jia; Wang, Le; Cheng, Zening; Lu, Libo; Guo, Liejin; Jin, Hui; Zhang, Deming; Wang, Runyu; Liu, Shanke
Abstract: The heating method of SCWG reactor is critical to system construction, and almost all existing reactors rely on external heat sources. In this article, the thermodynamic equilibrium model is established to predict the distribution of gasification products from supercritical water gasification of coal. The transformation rule of gas components in the SCWG process of coal and oxidation process of gasification products is explored. Especially, the influence of key parameters such as feedstock concentration, gasification temperature and pressure on the hydrogen yield during the gasification and oxidation processes is also discussed. Based on the above research, the autothermal gasification system for hydrogen production integrated supercritical water gasification of coal and oxidation of gasification products is proposed. The flow matching of supercritical water, coal slurry, and oxygen and its effect on the autothermal hydrogen yield are discussed. By optimizing the flow rate of the reactants, 80% of the hydrogen production efficiency is achieved. Highlights: Hydrogen production properties and influencing factors of SCWG are explored. Maximum hydrogen yield is investigated in the oxidation process. The hydrogen production efficiency of the proposed system can reach 80%.